Strategi Kepala Sekolah dalam Membina Disiplin Siswa di Madrasah Aliyah Al-Hidayah Sungai Bengkal Kabupaten Tebo - Sasmita Hasdiana; Shalahuddin Shalahuddin; Sodiah Sodiah (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to analyze the principal's strategy in fostering student discipline at Madrasah Aliyah Al-Hidayah Sungai Bengkal, Tebo Regency. Student discipline is a crucial aspect of character development and academic success. This research employs a qualitative approach with a case study method. Data collection techniques include observations, in-depth interviews, and documentation. The findings indicate that the principal implements various strategies such as enforcing school rules, instilling religious values, applying rewards and sanctions, and enhancing communication with parents. However, challenges exist, including students’ lack of awareness regarding the importance of discipline and limited school supervision. Therefore, this study recommends increasing the involvement of all stakeholders, including teachers and parents, to support student discipline development.